Sosialisasi Pengoptimalan dan Revitalisasi Potensi Wisata Berbasis Masyarakat Untuk Peningkatan Perekonomian Desa Di Desa Mojogebang Kecamatan Kemlagi Kabupaten Mojokerto - Sugeng Eko Yuli Waluyo; Setyaasih Setyaasih; Mohamad Johan Efendi; Khasbulloh Huda; Rachmad Sholeh (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service article aims to optimize and revitalize the various tourism potentials of Mojogebang village, especially the potential for community-based tourism to improve the economy of village residents. The efforts made are through formal outreach as well as ongoing direct approaches and guidance to village residents in realizing Mojogebang village as a community-based tourism village. Our findings in the field are that there are several tourism potentials that have not been explored and have not received optimal attention from policy makers, namely the local government. By involving Bumdes and Pokdarwis as well as the private sector and the wider community who are concerned about tourism potential, we are trying to involve active community participation to jointly realize the optimization and revitalization of village potential that has not been explored and touched by community creativity. The result of this community service is the emergence of awareness from all parties about the importance of exploring tourism potential in the village, and realizing it in concrete form regarding various superior village tourism which is able to make Mojogebang village one of the tourist village destinations.